MicroRNA-451 in chronic myeloid leukemia: miR-451-BCR-ABL regulatory loop? - Lopotová, Tereza; Záčková, Markéta; Klamová, Hana; Moravcová, Jana (Leukemia research, 2011)
Chronic myeloid leukemia (CML) is caused by constituve activity of BCR-ABL tyrosine kinase. Despite of high efficiency of imatinib, selective BCR-ABL inhibitor, about 30% of patients develop resistance. Novel markers and targets for therapy are thus necessary. MicroRNAs are small intereference RNAs whose role in physiological and malignant hematopoiesis has been shown. This study is focused on miR-451 in CML. Following our observation of miR-451 downregulation in CML, we further show its relation to BCR-ABL activity. Our data together with current literature indicate a more complex relationship of miR-451 and BCR-ABL in CML.
Keywords: Humans; bcr-abl fúzní proteiny; MicroRNAs; mikro RNA; geny abl; Genes, abl; chronická myeloidní leukemie; Fusion Proteins, bcr-abl; lidé; Leukemia, Myelogenous, Chronic, BCR-ABL Positive